A Study on Feature Analysis of English Guidebooks for Hokuriku Region in Japan Using Data Mining - Ban, Hiromi; Oyabu, Takashi (New Visions in Science and Technology Vol. 3, 2021)
The Hokuriku area of Japan includes Ishikawa Prefecture. One of the challenges facing Ishikawa's tourism is increasing the number of visitors from other nations. It should be important to provide “language service” to international tourists in order to tackle this problem. In order to understand the state of language service to foreign tourists, this study investigates what linguistic characteristics can be found in English guidebooks for Kanazawa, the capital city of Ishikawa, and Toyama, which is also in Hokuriku, and compares them to the official guidebooks published by the Japan National Tourist Organization for Tokyo, Fuji, Kyoto, and Hida. In summary, a C++ software is used to explore the frequency characteristics of character and word appearance. An exponential function is used to approximate these qualities. To determine the difficulty level and K-characteristic of each content, the percentage of Japanese junior high school necessary vocabulary and American basic vocabulary are computed. As a result, it is obvious that English guidebooks for Hokuriku have a similar trend in terms of character-appearance to literary texts.Furthermore, the K-characteristic values for them are high, and the difficulty level, particularly for Kanazawa, is low.